Política de educação especial no estado de Santa Catarina : formação em serviço do segundo professor - Bordin, Eleomara Oliveira de Moraes (2025)
This study analyzes the special education policy and in-service training in the provision of services to special education students in the state of Santa Catarina. The theme emerged from the need to understand the effectiveness of continuing education for teachers, especially second teachers, in school inclusion. The question that guides this research is: how does in-service training contribute to the role of second teachers, from the perspective of special education policy? The research discusses the historical evolution of inclusive policies and the state regulations that guide teaching practices in the state education system of Santa Catarina. The general objective is to analyze the special education policy for the state of Santa Catarina and the in-service training of second teachers in the provision of services to special education students in Santa Catarina. A qualitative approach is used, with documentary research and case study, including the application of questionnaires that were prepared for fifteen teachers who work as second teachers in three schools of the state education system that are located in the central region of the city of Chapecó, in the state of Santa Catarina. The analysis will be carried out based on questionnaires applied to teachers in the state education system of Santa Catarina. The study seeks to understand how in-service training contributes to the performance of the second teacher, from the perspective of special education policy. The main documents analyzed were the Political-Legal Frameworks for Special Education, Special Education Policy of SC (2017), and authors such as Mazzota (2017), Mantoan (2006), Minetto (2008), Mittler (2003). Therefore, it is expected that this research will contribute to reflections and improvements in training practices, strengthening the role of the second teacher in the construction of a truly inclusive school.